Quality of Life of Coronary Artery Disease Patients Based on the Degree of Physical Ability - Zuriati, Zuriati; Farida Moh. Said (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Coronary artery disease (CAD) is a chronic disease that can reduce the patient's quality of life (QoL). Decreased physical ability is one of the factors that can influence the QoL of CAD patients. Methods: This study used a cross-sectional descriptive design with a sample of 125 CAD patients aged 35-64 years at Dr. M. Djamil General Hospital Padang. QoL data was collected using the WHOQOL-BREF questionnaire, and the degree of physical ability was measured using the Duke Activity Status Index (DASI) questionnaire. Data analysis used the chi-square test. Results: The results showed that 43.8% of patients had good QoL, and 56.2% had very severe physical abilities. There is a significant relationship between the degree of physical ability and QoL in CAD patients (p-value 0.000). Conclusion: The degree of physical ability is a predictor of QoL in CAD patients. Interventions to improve physical abilities can help improve QoL in CAD patients.